Maps server: the example of Curucutu Nucieous SP - Queiroz Filho, Alfredo Pereira de (GEOUSP Espaço e Tempo (Online), 2003)
This paper is about an experience of implementation of a map server and deals with the characteristics of the publication in the Internet of a specific cartography database: the one of Curucutu and surroundings. The main advantages of its use include the fact that the software is free, that there is a wider range of alternatives as to making the maps available, that the access is free to all users and that operational procedures are very simple. The main negative aspects were the instability of the latest versions of the software and the size of the temporary files created